Is There a More Practical Way for Screening Minimal Hepatic Encephalopathy? - Değirmencioğlu Tosun, Şerife; Demirtaş, Coşkun Özer (Turkish Journal of Gastroenterology, 2023)
Cite this article as: Değirmencioğlu Tosun Ş, Demirtaş CÖ. Is there a more practical way for screening minimal hepatic encephalopathy? Turk J Gastroenterol. 2023;34(6):672.